The Intergenerational Transmission of Suicide: Moral Injury and the Mysterious Object in the Work of Walker Percy. (June 2016) - Tillman, Jane G.
The intrapsychic mechanisms for the intergenerational transmission of suicide are not adequately theorized, though it is well known that a family history of suicide places survivors at increased risk for suicide. The suicide of a family member, particularly a parent, it is hypothesized, marks some survivors with a type of trauma associated with moral injury, which may produce an alteration in object relations with the emergence of what may be called a mysterious object. Under the press of these conditions, survivors may embark on what Apprey (2014) has termed an "urgent errand" in an effort to solve a problem in the anterior generation. Analysands with a history of familial suicide may bring symptoms of moral injury, a mysterious object relation, and a risk for suicide into the transference. The family history, life history, and literary work of the novelist Walker Percy, who had an extensive family history of suicide, provides evidence for the hypothesis linking moral injury, a mysterious object, and an urgent errand in such patients.